EFFECTS OF A MICRNUTRIENT SUPPLEMENT (VCRESC EQ Ø\AC\(○,R)) ON VITAMIN AND HOMOCYSTEINE LEVELS IN END STAGE RENAL DISEASE PATIENT: 12 MONTH FOLLOW UP - Keizo Kanasaki; Kayo Yamamoto; Hitomi Sako; Akihiko Nakagawa; Hitoshi Yokoyama; Daisuke Koya (The Korean Society of Nephrology, 2012)
End stage renal disease (ESRD) patients may display the deficiency in vegetable-derived micronutrient, such as vitamins and minerals, due to the potassium-restricted diet. VCRESC, a drink type micronutrient supplement containing enough amounts of daily-required vitamins, is prescribed for patients with micronutrient deficiency in Japan. 58 years old woman under the chronic hemodialysis with non-diabetic ESRD. Before the initiation of VCRESC, her blood vitamins and Hcy levels were measured. She was introduced 125 ml/day of VCRESC oral intake over 12 months period. After first two weeks of VCRESC initiation, she was temporary advised to stop VCRESC for two weeks. Subsequently she was re-initiated VCRESC supplement until the end of the study. Her blood micronutrient levels were monitored at 2 and 4 weeks, 3 and 12 months after the initiation of study. Results: Some of her baseline blood vitamins (B6, B12, C) level exhibited lower when compared to Japanese standard value. After 2 weeks initiation of VCRESC, her vitamins (A, B1 B2, B6, B12, C and folate) levels elevated remarkably. After temporal termination of the VCRESC for 2 weeks, her vitamin B1, B2, C, E levels were suppressed, though vitamin A and B6 levels were not altered when compared to the levels observed at 2 weeks after the initiation of the study. At either 3 or 12 months after the initiation of study, vitamin B groups, E, C and folate was higher when compared to standard value; vitamin A levels remained in high standard range. Her Hcy level was higher than normal value in the beginning of study and reduced for 29% at the end of the study. Conclusion: Hcy level in dialysis patients has been shown to be an independent risk factor for vascular complications. VCRESC could be the potential nutritional intervention in the ESRD patient under chronic hemodialysis for the prevention of vascular complications.